Where monsters lie ebook - Starks, Kyle (Where Monsters Lie., 2023)
A brand-new meta-horror story that's Cabin in the Woods meets Tucker and Dale vs. Evil.Haven't you always wondered what slasher monsters—the masked home invasion family, the mindless unkillable monster, the serial killer trapped in a doll—what they do for those couple of years in-between their murder sprees? They're at Wilmhurst—a gated community in the middle of nowhere where they relax—or try to—until they get the call to go out and kill again.Connor Hayes survived his first slasher in summer camp. A handful of years later he barely escaped a psychopath who built torture puzzles for his victims. Since then he's been training and planning for running into these creatures again. He's a respected special agent. And now he knows where the monsters lie and he's planning for war.Collects Where Monsters Lie #1–#4.